Adaptation of wheat to climate change under different crop growing environment - KUMAR, SUNIL; KUMAR, BIRENDRA; TYAGI, SHASHANK (Journal of Soil and Water Conservation, 2017)
Field studies with variety K-9107 as normal sowing date variety under four dates of sowing (15 November to 06 December) and DBW-14 as late sowing date variety under five dates of sowing (13 December to 10 January) with one to four no. of irrigations at different critical stages as sub-plot were conducted during rabi seasons of 2010-11 and 2011-12 to study the phenology, accumulation of growing degree days (GDD), helio-thermal unit (HTU) and heat use efficiency (HUE) of wheat (Triticum aestivum L.) to select the proper combination of varieties, date of sowing and no. of irrigation and proper time of irrigation so that wheat crop could be adaptable to climate change in increasing temperature and scarcity of irrigation water. The grain yield was significantly higher for crop sown on November 15. The significant reduction in grain yield for less no. of irrigation was observed with delayed sowing. The crop sown on November 15 took maximum growing degree days, helio-thermal unit for ear emergence and maturity which was reduced significantly with subsequent delay in sowing time. Results revealed that HUE was maximum for grain yield and biomass for crop sown on November 15 and it was highest for crop with four no. irrigation and lesser HUE was recorded in delayed sowing with lesser no. of irrigated crop.